Voyerismo académico como síntoma del sistema contemporáneo de las ciencias sociales - Navarro Hinojoza, Ernesto (2023)
As never before, individuals can be exposed to an infinite amount of information and we can look and be looked at, where voyeurism stands as a fundamental part of modern socio-digital relationships that end up having a substantial influence beyond the digital world and transcend the sphere of the real. How much is this voyeuristic behavior becoming accentuated in the academy? How voyeuristic are we when we decide to "study, diagnose and analyze" rural environments and their problems and not go beyond that point? How aware are we being of it? And what repercussions does this position bring? Although it is not intended to give a definitive answer to any of these questions, the objective of this work is to make a self-criticism, highlighting the contradictions and processes facing the capitalocene that we are experiencing in our exercise as rural scholars. Making, in the first instance, a reflection on the voyeuristic culture in which we usually fall when seeking to be seen and recognized by our peers, and continuing with the analysis of our voyeuristic behavior in which we fall when trying to speak for and on behalf of the subjects study that we become objects by reifying them in our desktop analyses. Concluding that although this criticism is not new and generalizations are limiting, the mere fact that the phenomenon exists should motivate us to pause on the road and start questioning its direction.